2022
DOI: 10.1038/s41467-022-34000-6
|View full text |Cite
|
Sign up to set email alerts
|

MYC promotes immune-suppression in triple-negative breast cancer via inhibition of interferon signaling

Abstract: The limited efficacy of immune checkpoint inhibitor treatment in triple-negative breast cancer (TNBC) patients is attributed to sparse or unresponsive tumor-infiltrating lymphocytes, but the mechanisms that lead to a therapy resistant tumor immune microenvironment are incompletely known. Here we show a strong correlation between MYC expression and loss of immune signatures in human TNBC. In mouse models of TNBC proficient or deficient of breast cancer type 1 susceptibility gene (BRCA1), MYC overexpression dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 76 publications
(102 reference statements)
1
34
0
Order By: Relevance
“…However, we believe that Myc activity has not previously been linked to the expression of antigen presentation machinery. Interestingly, recent studies have described a direct role for Myc in the repression of interferon response genes in Nras G12D driven models of pancreatic ductal adenocarcinoma and triple negative breast cancer 53 , 54 . It is tempting to speculate that MYC-mediated suppression of mutant RAS driven activation of interferon signaling may be an unappreciated aspect of this cooperative oncogenic relationship that is exploited by cancers of all cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that Myc activity has not previously been linked to the expression of antigen presentation machinery. Interestingly, recent studies have described a direct role for Myc in the repression of interferon response genes in Nras G12D driven models of pancreatic ductal adenocarcinoma and triple negative breast cancer 53 , 54 . It is tempting to speculate that MYC-mediated suppression of mutant RAS driven activation of interferon signaling may be an unappreciated aspect of this cooperative oncogenic relationship that is exploited by cancers of all cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…A high number of TILs predicts favorable prognosis and pathological complete response in TNBC and HER2-enriched BC subtypes ( 61 ). TNBC patients with sparse or unresponsive tumor-infiltrating lymphocytes have limited efficacy of ICIs treatment ( 62 ). In the present study, patients with low IRS tended to have a higher infiltrating of CD8 T cells, activated NK cells and M1 Macrophages, which indicated that these patients had a better long-term survival than patients with high IRS and might be more suitable for ICI therapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe this is the first time that Myc activity has been linked to the expression of antigen presentation machinery. Interestingly, recent studies have described a direct role for Myc in the repression of interferon response genes in Nras G12D driven models of pancreatic ductal adenocarcinoma and triple negative breast cancer [55, 56]. It is tempting to speculate that Myc-mediated suppression of mutant RAS driven activation of interferon signaling may be an unappreciated aspect of this cooperative oncogenic relationship that is exploited by cancers of all cell lineages.…”
Section: Discussionmentioning
confidence: 99%